The Effect of Gross Domestic Product, Government Military Expenditure on Foreign Investment in ASEAN Countries - Rizqiah, Khairul; Julianus Pardede, Simon; Eko Saputro, Guntur; Iswati, Sri; Suwito Suwito (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The purpose of this study is to see the impact of Gross Domestic Product, Military Expenditure on Foreign Direct Investment in ASEAN countries. The results of this study show that GDP has a negative influence on foreign investment and the increase or decrease of Milex significantly affects foreign direct investment according to the political stability in each country. In some countries, it is said that increasing Milex does not necessarily make a country safer. An increase in Milex can occur when conflicts in a country or region increase and as a result investor confidence decreases. Whereas in other countries with higher political stability, descriptive statistics of military spending are used in this study and the data used in this study are from SIPRI, Word Bank, and data from the financial statements of ASEAN countries. Before the analysis, the constant value is, meaning that if the independent variable Milex is equal to zero, then the dependent variable (Foreign Investment) will have a value of 10.58533. The regression coefficient value of GDP (X1) is -0.180875 and Milex (X2) is 0.541519 and has a positive sign which means that if Milex increases by 1 unit, the dependent variable, namely Foreign Direct Investment, will also increase by 0.180875 and vice versa. it shows that the Jarque-Bera value is 67.16348 with a probability of 0.00000. The output result of the Adjusted R-Square value is 0.872961, or 87.29%.